Identifying the Coping Strategies of Nonoffending Pedophilic and Hebephilic Individuals From Their Online Forum Posts. (October 2021) - Jones, Sarah J.; Ó Ciardha, Caoilte; Elliott, Ian A.
Individuals who identify as pedophilic or hebephilic, and who do not offend, are increasingly visible in online discourse and as a focus of research. Developing knowledge about this population will offer insights into their psychological needs and, potentially, into the mechanisms and strategies individuals use to live offense-free lives. This study examined coping strategies among members of an online forum supporting pedohebephilic individuals who do not wish to offend. Forum users' posts were analyzed using thematic analysis. Eleven themes emerged, which were classifiable into three superordinate themes around (a) the acceptance of pedophilia, (b) strategies to stay safe, and (c) dealing with sexual arousal. These themes offer insight into the varying strategies used by these individuals to cope with stress and/or to remain offense-free. Understanding whether these strategies are adaptive or maladaptive may help develop better support services for those who have not offended and may inform prevention efforts.